Functional consequences of the transcallosal removal of intraventricular tumours. Issue 2 (February 1979) - Jeeves, M A; Simpson, D A; Geffen, G
Abstract : Colloid cysts and other benign tumours of the third and lateral ventricles may be exposed through a small incision in the body of the corpus callosum. This approach is practicable even when ventricular dilatation is slight, and is theoretically less likely to cause epilepsy than the more usual transcortical approach. Disturbances of memory have been noted soon after such operations, but do not cause serious long-term disability. Three patients who underwent transcallosal removal of cysts or tumours some years earlier have been tested by procedures designed to demonstrate interhemispheric transfer of information: they were all found to have defects in transfer of tactile data, but not of information obtained visually. They were not aware of this inability, and do not appear to be inconvenienced by it. The transcallosal route is convenient. The operation sacrifices a functionally significant part of the corpus callosum, but the neurological sequelae have seemed acceptable. However, especially in the elderly, stereoventriculoscopic aspiration may be considered as the initial method of treatment.